(untitled) (Research, Society and Development, 2020)
Introduction: one of the challenges for institutions with graduation in medicine is to structure the medical education based on the National Curriculum Guidelines established in 2014. Another aspect to be considered is the satisfaction of former students with the education received which may interfere on professional autonomy and self-confidence. Objective: to know the meaning of received education in the view of doctors graduated from a Federal University in Southern Brazil. Method: this is a qualitative, exploratory-descriptive research conducted with 51 graduates through a self-administered online questionnaire with 26 questions. The findings were analyzed using Bardin’s Content Analysis. Results: the categories representing the meanings of received education, in the view of the graduates, were: humanization in their graduation, related to teachers and humanized care for patient; satisfaction with quality of teaching, giving security and trust through knowledge to perform the profession. The underlined weaknesses were insufficiently content, excessive demands, and teaching fragmentation. Conclusions: medical education in the view of former students was full of meanings embracing all the exercise of profession. It is necessary that managements of medical schools consider the students’ view to qualify the received education.